(untitled) (New York, 1990)
This book is presented about a review of basic grammatical structures and terms; functions skill, and activities; auxiliary verbs and present tenses,....
Keywords: English language,English language; Textbooks for foreign speakers.,Grammar,Problems, exercises, etc